2004
DOI: 10.1088/0953-2048/17/7/018
|View full text |Cite
|
Sign up to set email alerts
|

Melt textured YBa2Cu3Oybulks with artificially patterned holes: a new way of processingc-axis fault current limiter meanders

Abstract: YBa2Cu3Oy (Y123) bulk materials were textured with artificially patterned holes, creating a ‘perforated structure’. The goal is to facilitate sample oxygenation and decrease crack formation in order to address the problem of hot spot formation in fault current limiter (FCL) applications. As-processed samples contained mechanically patterned holes parallel to the mean c-axis interconnected to the textured domain. This makes samples easier to oxygenate and cool. The microstructure is not distorted in the vicini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 15 publications
3
48
0
Order By: Relevance
“…Those measurements have shown that the texture development in the total volume, as seen macroscopically, is not influenced by the presence of holes in the pellet [26]. At the same time, SEM microscopic observations indicate that the local microstructure is preserved even in the vicinity of holes.…”
Section: Artificially Patterned Holed Tsmtgmentioning
confidence: 89%
See 1 more Smart Citation
“…Those measurements have shown that the texture development in the total volume, as seen macroscopically, is not influenced by the presence of holes in the pellet [26]. At the same time, SEM microscopic observations indicate that the local microstructure is preserved even in the vicinity of holes.…”
Section: Artificially Patterned Holed Tsmtgmentioning
confidence: 89%
“…The powder mixture was pelletized uniaxially and then sintered at 920 • C for 24 h. Regularly spaced 1 mm diameter holes were drilled into sintered bulk samples before the standard melt process is operated. After the growth step, the samples were submitted to an additional annealing under oxygen flow at 450 • C for 150 h in order to obtain good superconducting properties [26,28].…”
Section: Tsmtg Process With Artificially Patterned Holesmentioning
confidence: 99%
“…For meandering FCL elements, cutting is a crucial step as cracks appear during this stage. This can be solved by the in situ zigzag shape processing of holes, as we demonstrated the feasibility of elsewhere [43]. magnetization using a homemade large dc current source.…”
Section: (A (B) (C)mentioning
confidence: 99%
“…Another unique aspect concerning flux trapping is to distribute holes drilled within the bulk pack. The recently reported [41][42][43][44][45] hole-patterned YBa2Cu3Oy (Y123) bulks with improved superconducting properties are highly interesting from the points of view of material quality and their variety of application. It is well known that the core of plain bulk superconductors needs to be fully oxygenated, and some defects like cracks, pores and voids [46,47] must be suppressed in order that the material can trap a high magnetic field or else carry a high current density.…”
Section: Gd211 Bazro3mentioning
confidence: 99%
See 1 more Smart Citation